Intragrain oxygen isotope zoning in titanite by SIMS: Cooling rates and fluid infiltration along the Carthage‐Colton Mylonite Zone, Adirondack Mountains, NY, USA. (13th December 2013) - Bonamici, C. E.; Kozdon, R.; Ushikubo, T.; Valley, J. W.
Abstract Oxygen isotopes are an attractive target for zoning studies because of the ubiquity of oxygen‐bearing minerals and the dependence of mineral 18O/16O ratios on temperature and fluid composition. In this study, subtle intragrain oxygen isotope zoning in titanite is resolved at the 10‐μm scale by secondary ion mass spectrometry. The patterns of δ18O zoning differ depending on microstructural context of individual grains and reflect multiple processes, including diffusive oxygen exchange, partial recrystallization, grain‐size reduction, and grain growth. Using the chronological framework provided by structural relations, these processes can be related to specific events during the Grenville orogeny. Titanite was sampled from two outcrops within the Carthage‐Colton Mylonite Zone (CCMZ), a long‐lived shear zone that ultimately accommodated exhumation of the Adirondack Highlands from beneath the Adirondack Lowlands during the Ottawan phase (1090–1020 Ma) of the Grenville orogeny. Titanite is hosted in the Diana metasyenite complex, which preserves three sequentially developed fabrics: an early NW‐dipping protomylonitic fabric (S1) is crosscut by near‐vertical ultramylonitic shear zones (S2), which are locally reoriented by a NNW‐dipping mylonitic fabric (S3). Texturally early titanite (pre‐S2) shows diffusion‐dominated δ18O zoning that records cooling from peak Ottawan, granulite‐facies conditions. Numerical diffusion models in the program Fast Grain Boundary yield good fits to observed δ18O profiles for cooling rates of 50 ± 20 °C Ma−1, which are considerably faster than the 1–5 °C Ma−1 cooling rates previously inferred for the Adirondack Highlands from regional thermochronology. High cooling rates are consistent with an episode of rapid shearing and exhumation along the CCMZ during gravitational collapse of the Ottawan orogen at c. 1050 Ma. Texturally later titanite (syn‐S2) has higher overall δ18O and shows a transition from diffusion‐dominated to recrystallization‐dominated δ18O zoning, indicating infiltration of elevated‐δ18O fluids along S2 shear zones and continued shearing below the blocking temperature for oxygen (~≤500 °C for grain sizes at the study site). The texturally latest titanite (post‐S3) has growth‐dominated δ18O zoning, consistent with porphyroblastic grain growth following cessation of shearing along the Harrisville segment of the CCMZ.